TINGKAT KEPEMILIKAN RUMAH DI INDONESIA - Atu Bagus Wiguna; Kintan Terate Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Government policies related to public housing have not been able to overcome the high backlog of home ownership in Indonesia. This is constrained by various problems such as housing affordability and differences in access to housing due to gaps in infrastructure development between regions in Indonesia. This study aims to analyse the effect of credit and residential property prices, income and unemployment on the home ownership rate in Indonesia. Using a descriptive quantitative approach with 3 models estimated by the multiple regression method of panel data.The secondary data used is aggregate data of provinces in Indonesia. The home ownership rate is higher in Eastern Indonesia compared to Western Indonesia, this is due to the unemployment rate in Western Indonesia which is higher than Eastern Indonesia. Although assisted by a higher average residential property credit than the average residential property credit in Eastern Indonesia does not make the average home ownership rate in Western Indonesia higher. It may be constrained by lower average income and higher average property prices than Eastern Indonesia so that the risk of default is also higher in Western Indonesia which can eliminate ownership rights from homes purchased through mortgages.